Infection - The Comrade of Acute Pancreatitis in Systemic Lupus Erythematosus: A Case Series from Single Tertiary Centre in India - Israrul Haque; Parasar Ghosh; Geetabali Sircar; Biswadip Ghosh; Pradyot Sinhamahapatra (Journal of Clinical Rheumatology and Immunology)
Introduction: Acute Pancreatitis in systemic lupus Erythematous is rare but has high mortality. Incidence varies from 1-5% and reported mortality is 3-37.04% with mortality being higher in juvenile SLE. Objective: Study of Clinical and serological profile of SLE patients presenting with acute pancreatitis. Method: Retrospective data of SLE patients visiting our institution was collected. Diagnosis was considered if patients had clinical + biochemical and radiological evidence of pancreatitis. Patients with diagnosis of gallstone, history of alcohol intake, serum Triglycerides>500 mg/dl, serum calcium>10.5 mg/dl and taking Azathioprine at the time of diagnosis were excluded. Results: 9 patients fulfilled inclusion and exclusion criteria. 7 had severe and 2 had moderately severe acute pancreatitis. Female: Male ratio was 8:1, Median age was 25(15-50) years, Median disease duration 12 months (3-48), 4(44.45%) presented within 1 year of disease onset. Mean SELENA-SLEDAI at the time of presentation was 26(19-41). 4(44.45%) were on corticosteroids at the time of presentation. Other active domains at the time of diagnosis were Nephritis in 7(77.78%), NPLE in 3(33.34%), Myositis in 4(44.45%), Autoimmune haemolytic anaemia in 2 (22.22%), Macrophage activation syndrome in 4 (44.45%) enteritis in 1 (11.11%) Myocarditis in 2 (22.22%) and Mucocutaneous in 9 (100%) patients. All patients had elevated Serum Amylase and Lipase level with Median serum Amylase being 545 Units/Litre (normal[Formula: see text]176) and median serum Lipase being 511 ([Formula: see text]160) Units/litre. 6(66.67%) had hypocalcemia and 5 (55.56%) had hypertriglyceridemia. Raised dsDNA was seen in 9(100%, median 277 IU/ml) and hypocomplementemia was seen in 7(77.78%, Median C3 value 49 mg/dL)). None of the patients had associated antiphospholipid syndrome but persistent antiphospholipid antibodies were present in 5(55.56%)-4 had lupus anticoagulant and 1 had Anticardiolipin antibody. 6(66.67%) patients had microbiologically confirmed infection the time of diagnosis of acute pancreatitis (4 bacterial and 1 fungal) among which 3 had lower respiratory tract infection, 1 had urinary tract infection, 1 had pseudomembranous colitis and 1 had peri-pancreatic abscess. 7 patients received only corticosteroids, and 2 patients received IVIG with corticosteroids. 3 out of 9 patients (33.34%) expired due to multi-organ failure. Out of 6 surviving patients all received IV cyclophosphamide (NIH protocol) and are doing fine. Conclusion: Acute pancreatitis in SLE has high mortality probably due to associated high clinical and serological disease activity and high incidence of concomitant infection. Extensive investigation for underlying infection (bacterial, viral and fungal) should be done in SLE patients presenting with acute pancreatitis for comprehensive management.